Gender differences in mental health status among children aged three to six years - Wu, Shin Ling; Abdullah, Rohani; Mofrad, Sakineh (Universiti Putra Malaysia Press, 2014)
This study was designed to examine the gender differences in children's mental health. A total of 427 children (205 male and 222 female) aged between 3 to 6 years old were recruited from 29 pre-schools in Malaysia using cluster sampling technique. Children's mental health status was measured by using Achenbach & Rescorla's Child Behavior Checklist 1.5-5(CBCL/1.5-5),which comprised of eight subscales. The CBCL is administered to the parents to answer regarding their child over a week's period. The findings revealed no significant gender differences on the overall mental health score and all its subscale scores, except for aggressive behavior. Boys had a higher mean score on aggressive behavior, compared to girls. This means that boys tended to be more aggressive than girls. Early detection of mental health and identification of the risk factors of mental health is crucial to understand the behavior of children.